Complete remission of depression and anxiety using a ketogenic diet: case series - Calabrese, Lori; Frase, Rachel; Ghaloo, Mariam (Frontiers in Nutrition, 2024)
Background: There is little data which describes the use of ketogenic metabolic therapy to achieve full remission of major depression and generalized anxiety disorder in clinical practice. We present a retrospective case series of three adults with major depression and generalized anxiety disorder with complex comorbidity, treated with personalized ketogenic metabolic therapy who achieved complete remission of major depression and generalized anxiety disorder, and improvements in flourishing, self-compassion, and metabolic health. Methods: Three adults, ages 32-36, with major depression, generalized anxiety, other anxiety disorders and comorbid psychiatric conditions were treated for 12-16 weeks with a personalized whole foods animal-based ketogenic metabolic therapy (1.5:1 ratio) in a specialized metabolic psychiatry practice. Interventions included twice-weekly visits with an experienced ketogenic registered dietitian, daily photo journaling and capillary blood BHB/glucose/GKI monitoring, groups, family/friends supports, nature walks and talks several, and community building. Successful adoption of the ketogenic diet was defined as achievement and maintenance of capillary BHB > 0.8 mmol/L and GKI < 6. Remission was assessed by GAD-7 and PHQ-9, quality of life was assessed subjectively and with validated scales for Flourishing and Self-Compassion. Metabolic health was assessed by laboratories/biometric measures. Results: Two patients achieved remission of major depression (PHQ-9 < 4) and generalized anxiety (GAD-7 < 1) within 7 weeks of therapeutic nutritional ketosis; one required 12 weeks. Anxiety responded and remitted more quickly than major depression. Flourishing and selfcompassion increased steadily. Patients lost 10.9 to 14.8% of initial body weight within 12 weeks, and improved metabolically; one achieved optimal metabolic health. Conclusion: Complete remission of major depression and generalized anxiety disorder occurred within 7-12 weeks of therapeutic nutritional ketosis during treatment with a personalized animalbased ketogenic diet (ratio 1.5:1) in adults with complex comorbid depression and anxiety engaged in a specialized metabolic psychiatry program.